Value-Based Islamic Economics and Sustainable Development: A Systematic Literature Review - Rahmatul Fitria (SHACRAL: Shari'ah Economics Review Journal, 2026)
The integration of ethical and value-based principles into development frameworks has gained growing attention amid persistent global challenges including income inequality, financial exclusion, and environmental degradation. Islamic economics, grounded in the ethical imperatives of the Quran and Sunnah, offers a normative and operational framework that aligns closely with the objectives of sustainable development. This study presents a systematic literature review examining the relationship between Islamic economics and sustainable development, synthesizing peer-reviewed journal articles, books, and institutional reports published between 2015 and 2024. Using qualitative thematic analysis, the review identifies key conceptual linkages across five major themes: (1) the conceptual convergence between Islamic economics and the Sustainable Development Goals (SDGs); (2) the role of maqashid al-shariah as a holistic development framework; (3) economic justice and distributive mechanisms; (4) the contribution of Islamic finance to sustainable economic growth; and (5) Islamic social finance as a tool for poverty alleviation. Findings demonstrate that Islamic economics provides a robust ethical architecture that is compatible with and complementary to the SDG framework. Instruments such as zakat, waqf, and Islamic banking foster financial inclusion, reduce inequality, and promote socially responsible growth. The study concludes that realizing the full transformative potential of Islamic economics requires stronger policy integration, institutional capacity building, and governance reform, particularly in Muslim-majority developing countries.